2000
DOI: 10.1097/00004770-200005000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Flow Rate of Newer and Established Root Canal Sealers

Abstract: Endodontic sealers that possess both optimum flow ability and antimicrobial properties may theoretically assist in the elimination of microorganisms located in confined areas of the root canal system. The antimicrobial effects and the flow rate of the following sealers were investigated and compared: Kerr Pulp Canal Sealer EWT, Grossman's Sealer, ThermaSeal, Sealer 26, AH Plus, and Sealer Plus. The agar diffusion test was used to assess the antimicrobial activity of the sealers. In the flow assay, the sealers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
3
15

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(155 citation statements)
references
References 14 publications
(5 reference statements)
6
122
3
15
Order By: Relevance
“…Since in this situation the extent of the inhibition zone does not necessarily reflect the strength of the antimicrobial agent, the data corresponding to the antimicrobial activity of each material were analyzed statistically using the Kruskal-Wallis and Dunn tests, as advised by Siqueira et al (22).…”
Section: Discussionmentioning
confidence: 99%
“…Since in this situation the extent of the inhibition zone does not necessarily reflect the strength of the antimicrobial agent, the data corresponding to the antimicrobial activity of each material were analyzed statistically using the Kruskal-Wallis and Dunn tests, as advised by Siqueira et al (22).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies on the effect of materials used in odontology on Candida genus yeasts are rarely found. Siqueira Junior et al 26 , studying the antimicrobial activity of root canal sealers, concluded that a eugenol-containing sealer showed relative effectiveness against Candida, but this action was observed only after a long time interval (40 days). Also Kaplan et al 8 , analyzing the antimicrobial effect of endodontic sealers, concluded that eugenol was effective against Candida cells.…”
Section: Discussionmentioning
confidence: 99%
“…AH Plus, an epoxy resin amine sealer, was used to carry out the obturation process because the flow of AH Plus is significantly higher than other sealers tested. 28 Balguerie et al 29 evaluated…”
mentioning
confidence: 99%